Lokal yrkesfagskultur og ulikhet i fortellinger om ungdoms utdanningsvalg : - et stedssensitivt blikk på Oslo og Rogaland - Hegna, Kristinn; Reegård, Kaja (Nordic Journal of Comparative and International Education (NJCIE), 2019)
The literature on vocational educational aspirations typically lacks a conception of space, place and local employment opportunities. This article compares two locations in Norway, that is, the capital Oslo, characterised by knowledge-intensive industries, and a rural district in Rogaland, characterised by manufacturing and oil-related industries, to illuminate how aspirations, class and location intersects. In Oslo, there is a lack of available apprenticeships, a strong east-west segregation regarding enrolment to vocational education and training, and few schools provide vocational programs. In contrast, Rogaland has a firmly established vocational culture, and large shares of youth opt for vocational educations following ten years of compulsory schooling. Drawing on interviews with young people in Oslo and Rogaland, the case-comparative analysis illustrates how these two locations are (re)producing very different educational logics, directing youth either away from or towards vocational education. The article aims to contribute to understandings of educational aspirations by advocating place-sensitivity in the complex ways that social inequality in education is shaped, maintained and reinforced.